Plate-like spinel particles and method for producing same
Patent Information
- Application Number
- JP2020565200
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-11
- Filing Date
- 2020-01-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-01-09
AI Technical Summary
【0009】 上記態様の板状スピネル粒子及びその製造方法によれば、誘電正接を低く保ちながら、優れた機械強度を有する板状スピネル粒子を提供することができる。
Smart Images

Figure 0007622435000002 
Figure 0007622435000001
Abstract
Description
[Technical field]
[0001] The present invention relates to plate-like spinel particles and a method for producing the same. [Background technology]
[0002] Inorganic particles with a plate-like shape and a high aspect ratio have particularly excellent thermal and optical properties due to their unique shape. Currently, in the fields of automobiles and electronic components, there is a demand for inorganic fillers with excellent physical properties such as low dielectric constant (dielectric constant), Q value or dielectric tangent, mechanical strength, thermal conductivity, and thermal expansion coefficient, and inorganic particles with a high aspect ratio as described above are attracting attention. An example of an inorganic particle with an aspect ratio is plate-like alumina, and various research is being conducted on improving thermal conductivity and mechanical strength. However, the inherent dielectric tangent of alumina is only 10 -3 Therefore, it is impossible to obtain a material that has both a low dielectric tangent in addition to high thermal conductivity and mechanical strength.
[0003] On the other hand, examples of inorganic particles having a low dielectric constant include spinel particles of a double oxide of metal elements represented by MgAl2O4 and having a general formula AB2X4. Patent Documents 1 and 2 disclose spinel particles having excellent thermal conductivity.
[0004] However, while there are cases in which conventional spinel particles disclosed in Patent Documents 1, 2 and the like have been obtained that have a large crystallite size, excellent thermal conductivity of the particles themselves, and a low dielectric tangent or excellent chemical resistance, no particles have yet been found that have a low dielectric tangent, a high aspect ratio, and excellent mechanical strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2016-135841 [Patent Document 2] International Publication No. 2017 / 221372 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in view of the above circumstances, and provides plate-like spinel particles having excellent mechanical strength while maintaining a low dielectric tangent, and a method for producing the same. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted extensive research in order to achieve the above object, and as a result have found that spinel particles obtained by firing molybdenum-containing plate-like α-alumina particles and a magnesium compound not only have a high aspect ratio and excellent mechanical strength, but also have large crystallite diameters, excellent thermal conductivity, and a plate-like shape with an extremely small dielectric tangent, thereby completing the present invention.
[0008] That is, the present invention includes the following aspects. (1) Plate-like spinel particles having a thickness T of 0.01 μm or more and 5 μm or less, an average particle size L of 0.1 μm or more and 500 μm or less, an aspect ratio L / T of 3 or more and 500 or less, and containing molybdenum within the particles. (2) The plate-like spinel particles according to (1), wherein the molybdenum content is from 0.01% by mass to 1% by mass in terms of molybdenum trioxide, relative to 100% by mass of the plate-like spinel particles. (3) The plate-like spinel particles according to (1) or (2), having a crystallite diameter of 60 nm or more calculated from the half-width of a diffraction peak corresponding to a (311) plane obtained by X-ray diffraction method. (4) The method for producing plate-like spinel particles is a method for producing plate-like spinel particles according to any one of (1) to (3), which comprises calcining a magnesium compound and an aluminum compound in the presence of molybdenum. (5) The method according to (4), wherein the aluminum compound is plate-like alumina particles. (6) The method according to (4) or (5), wherein the aluminum compound contains molybdenum in an amount of 0.1% by mass or more and 1% by mass or less in terms of molybdenum trioxide. (7) The method according to any one of (4) to (6), wherein a sodium compound or a potassium compound is used as a shape control agent during firing. (8) The method according to any one of (4) to (7), wherein the firing is carried out at a temperature of less than 1,300° C. (9) The method according to any one of (4) to (8), wherein the aluminum compound and the magnesium compound have an average particle size of 1 μm or more and 10 μm or less. Effect of the Invention
[0009] According to the above-described embodiment of the plate-like spinel particles and the method for producing the same, it is possible to provide plate-like spinel particles that have excellent mechanical strength while maintaining a low dielectric tangent. [Brief description of the drawings]
[0010] [Figure 1] 1 shows SEM images of spinel particles obtained in Examples and Comparative Examples. The scale bar (solid line) in (A) to (E) is 10.0 μm. The scale bar (dotted line) in (F) is 50.0 μm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, a plate-like spinel particle and a method for producing the same according to one embodiment of the present invention will be described in detail.
[0012] <Plate-shaped spinel particles> The plate-like spinel particles according to the embodiment have a thickness T of 0.01 μm or more and 5 μm or less, an average particle diameter L of 0.1 μm or more and 500 μm or less, and an aspect ratio L / T of 3 or more and 500 or less. In addition, the plate-like spinel particles according to the embodiment contain molybdenum within the particles.
[0013] Generally, "spinel particles" contain magnesium atoms, aluminum atoms, and oxygen atoms, and are therefore usually represented by the chemical composition MgAl2O4. The plate-like spinel particles according to the embodiment contain molybdenum within the particles, and the form of molybdenum inclusion is not particularly limited, but includes a form in which molybdenum is attached to, coated on, or bonded to the surface of the spinel particles, or arranged in a similar form, a form in which molybdenum is incorporated into the spinel, and a combination thereof. In this case, examples of the form in which molybdenum is incorporated into the spinel include a form in which at least a part of the atoms constituting the spinel particles is replaced with molybdenum, and a form in which molybdenum is arranged in a space (including a space caused by a defect in the crystal structure) that may exist inside the crystal of the spinel particle. In the above-mentioned form of replacement, the atom constituting the spinel particle to be replaced is not particularly limited, and may be any of magnesium atoms, aluminum atoms, oxygen atoms, and other atoms. In particular, molybdenum is preferably contained in a form in which it is at least incorporated into the spinel. When molybdenum is incorporated into the spinel, it tends to be difficult to remove by, for example, washing.
[0014] The plate-like spinel particles according to the embodiment can have excellent mechanical strength while maintaining a low dielectric loss tangent due to the above shape. Conventional spinel particles, as shown in the examples described later, do not satisfy at least one of the requirements of the above thickness, average particle size, and aspect ratio. Therefore, conventional spinel particles have low dielectric loss tangent but poor mechanical strength, probably because they are not plate-like or have a small particle size. The plate-like spinel particles according to the embodiment have a particularly high aspect ratio, and are therefore believed to be capable of exhibiting excellent mechanical strength.
[0015] In this specification, the "aspect ratio" is the ratio of the average particle diameter of the spinel particles divided by the thickness. In addition, "plate-like" here refers to an aspect ratio of 2 or more. In this specification, the "thickness of the spinel particles" is the arithmetic mean value of the thicknesses measured for at least 50 spinel particles randomly selected from an image obtained by a scanning electron microscope (SEM). The "particle diameter" is the maximum length between two points on the outline of the spinel particle. The "average particle diameter of the spinel particles" is the arithmetic mean value of the particle diameters measured for at least 50 plate-like spinel particles randomly selected from an image obtained by a scanning electron microscope (SEM).
[0016] The plate-like spinel particles according to the embodiment have a thickness of 0.01 μm to 5 μm, preferably 0.05 μm to 3 μm, more preferably 0.1 μm to 1 μm, even more preferably 0.15 μm to 0.75 μm, particularly preferably 0.2 μm to 0.5 μm, and most preferably 0.2 μm to 0.47 μm. By having the thickness of the plate-like spinel particles within the above range, the mechanical strength can be improved.
[0017] The plate-like spinel particles according to the embodiment have an average particle size of 0.1 μm to 500 μm, preferably 0.3 μm to 100 μm, more preferably 0.5 μm to 50 μm, even more preferably 1 μm to 30 μm, even more preferably 1 μm to 20 μm, particularly preferably 1 μm to 10 μm, and most preferably 4 μm to 9 μm. By having the average particle size of the plate-like spinel particles be equal to or greater than the lower limit, it is possible to more effectively suppress an increase in viscosity when mixed with a resin or the like, while by having the average particle size be equal to or less than the upper limit, it is possible to make the surface of a molded article containing the plate-like spinel particles smoother.
[0018] The tabular spinel particles according to the embodiment have an aspect ratio of 3 or more and 500 or less, preferably 5 or more and 100 or less, more preferably 7 or more and 50 or less, even more preferably 9 or more and 30 or less, even more preferably 10 or more and 25 or less, particularly preferably 12 or more and 23 or less, and most preferably 14.5 or more and 20 or less. When the aspect ratio is equal to or more than the above lower limit, the mechanical strength tends to be excellent, while when the aspect ratio is equal to or less than the above upper limit, the surface of a molded article containing the tabular spinel particles can be made smoother.
[0019] Regarding the preferred spinel particle shapes described above, the conditions of thickness, average particle size, and aspect ratio can be combined in any manner as long as the particles are plate-like.
[0020] The plate-like spinel particles according to the embodiment may be circular or elliptical plate-like, but the particle shape is preferably polygonal, for example, hexagonal to octagonal, from the standpoints of characteristics such as dielectric loss tangent, ease of handling, ease of production, and the like.
[0021] The crystallite size of the (311) plane of the plate-like spinel particles according to the embodiment is preferably 60 nm or more, more preferably 65 nm or more, even more preferably 66 nm or more, and even more preferably 70 nm or more. On the other hand, there is no particular upper limit to the crystallite size of the (311) plane, and it can be, for example, 200 nm or less, 150 nm or less, 100 nm or less, 90 nm or less, or 82 nm or less. Here, the (311) plane is one of the main crystal domains of the spinel particles, and the size of the crystal domain of the (311) plane corresponds to the crystallite diameter of the (311) plane. The larger the crystallite diameter, the higher the density and crystallinity of the particle, which means that there is no disordered part where phonons are scattered, and therefore the thermal conductivity is high. The crystallite diameter of the (311) plane of the spinel particles can be controlled by appropriately setting the conditions of the manufacturing method described later. In addition, in this specification, the value of the "crystallite diameter of the (311) plane" is a value calculated using the Scherrer formula from the half-width of the peak (peak appearing around 2θ=37 degrees) belonging to the (311) plane measured using X-ray diffraction (XRD). In addition, "around 37 degrees" here means a range of 37 degrees ±0.5 degrees.
[0022] As described above, the spinel particles contain magnesium atoms, aluminum atoms, and oxygen atoms, and are generally represented by the composition MgAl2O4. The plate-like spinel particles according to the embodiment contain molybdenum. The plate-like spinel particles according to the embodiment may also contain other inevitable impurities, other atoms, etc., as long as they do not impair the effects of the present invention.
[0023] <Content of each atom> The content of magnesium atoms in the spinel particles is not particularly limited, but for example, when the molar amount of aluminum atoms is 2 moles, the content is preferably 0.8 moles or more and 1.2 moles or less, and more preferably 0.9 moles or more and 1.1 moles or less. The content of aluminum atoms in the spinel particles is not particularly limited, but for example, when the molar amount of magnesium atoms is taken as 1 mol, it is preferably 1.8 mol or more and 2.2 mol or less, and more preferably 1.9 mol or more and 2.1 mol or less. The contents of magnesium atoms and aluminum atoms in the spinel particles can be measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). The content of oxygen atoms in the spinel particles is not particularly limited, but is determined according to the molar amounts of magnesium atoms and aluminum atoms. For example, when the magnesium atoms and aluminum atoms are 1 mol and 2 mol, respectively, the content of oxygen atoms in the spinel particles is preferably 3.8 mol or more and 4.2 mol or less, more preferably 3.9 mol or more and 4.1 mol or less.
[0024] <Molybdenum> Molybdenum may be contained as a result of the production method described below.
[0025] The molybdenum is not particularly limited, and in addition to molybdenum metal, it includes molybdenum oxide, partially reduced molybdenum compounds, etc. Molybdenum is considered to be contained in the plate-like spinel particles as MoO3, but may also be contained in the plate-like spinel particles as MoO2, MoO, etc., other than MoO3.
[0026] The form in which molybdenum is contained is not particularly limited, and it may be contained in a form in which it is attached to, coated on, bonded to, or disposed in a similar manner on the surface of the plate-like spinel particle, or it may be contained in a form in which molybdenum is incorporated into the spinel, or a combination of these.
[0027] The molybdenum content is not particularly limited, but from the viewpoint of high thermal conductivity of the plate-like spinel particles according to the embodiment, it is preferably 1 mass% or less, more preferably 0.8 mass% or less, in terms of molybdenum trioxide, relative to 100 mass% of the plate-like spinel particles, and from the viewpoint of higher density of the plate-like spinel particles, it is even more preferably 0.7 mass% or less, even more preferably 0.65 mass% or less, and particularly preferably 0.61 mass% or less. On the other hand, the lower limit of the molybdenum content is not particularly limited, but can be, for example, 0.01 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0.15 mass% or more, 0.2 mass% or more, 0.25 mass% or more, or 0.31 mass% or more. In this specification, the molybdenum content in the plate-like spinel particles can be determined by XRF analysis. The XRF analysis is performed under the same conditions as the measurement conditions described in the examples described later, or under compatible conditions that give the same measurement results.
[0028] <Inevitable impurities> Inevitable impurities are impurities that are present in raw materials or that are inevitably mixed into the tabular spinel particles during the production process, and are essentially unnecessary, but are present in trace amounts and do not affect the properties of the tabular spinel particles.
[0029] The inevitable impurities are not particularly limited, but include silicon, iron, potassium, sodium, calcium, etc. These inevitable impurities may be contained alone or in combination of two or more kinds.
[0030] The content of unavoidable impurities in the tabular spinel particles is preferably 10,000 ppm or less, more preferably 1,000 ppm or less, and even more preferably 10 ppm or more and 500 ppm or less, based on the mass of the tabular spinel particles.
[0031] <Other atoms> The other atoms refer to atoms that are intentionally added to the spinel particles for the purposes of coloring, luminescence, controlling the formation of spinel particles, and the like, within the scope of not impairing the effects of the present invention.
[0032] The other atoms are not particularly limited, but include zinc, cobalt, nickel, iron, manganese, titanium, zirconium, calcium, strontium, yttrium, etc. These other atoms may be used alone or in combination of two or more.
[0033] The content of other atoms in the tabular spinel particles is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less, based on 100% by mass of the tabular spinel particles.
[0034] <Method for producing plate-shaped spinel particles> The method for producing the plate-like spinel particles according to the embodiment is not particularly limited and known techniques can be appropriately applied, but a production method including a step of calcining a magnesium compound and an aluminum compound in the presence of molybdenum (calcination step) is preferred. The calcination step may be a step of calcining a mixture obtained in a step of obtaining a mixture to be calcined (mixing step).
[0035] <Mixing process> The mixing step is a step of mixing raw materials such as a magnesium compound, an aluminum compound, and molybdenum to obtain a mixture. In this case, the mixed state of the magnesium compound and the aluminum compound is not particularly limited. When mixing the two, simple mixing of mixing powders, mechanical mixing using a grinder or mixer, mixing using a mortar, etc. are performed. In this case, the obtained mixture may be in either a dry state or a wet state, but is preferably in a dry state from the viewpoint of cost.
[0036] In the mixing step, the mixing ratio of the magnesium compound and the aluminum compound is not particularly limited, but they are preferably mixed so that the molar ratio of the magnesium element of the magnesium compound to the aluminum element of the aluminum compound (aluminum element / magnesium element) is 1.8 or more and 2.2 or less, and more preferably 1.9 or more and 2.1 or less. The contents of the mixture will be described below.
[0037] [Magnesium compounds] The magnesium compound is not particularly limited, and examples thereof include metallic magnesium, magnesium derivatives, magnesium oxoacid salts, magnesium organic salts, and hydrates thereof. Examples of magnesium derivatives include magnesium oxide, magnesium hydroxide, magnesium peroxide, magnesium fluoride, magnesium chloride, magnesium bromide, magnesium iodide, magnesium hydride, magnesium diboride, magnesium nitride, magnesium sulfide, and the like. Examples of magnesium oxoacid salts include magnesium carbonate, calcium magnesium carbonate, magnesium nitrate, magnesium sulfate, magnesium sulfite, magnesium perchlorate, trimagnesium phosphate, magnesium permanganate, magnesium phosphate, and the like. Examples of magnesium organic salts include magnesium acetate, magnesium citrate, magnesium malate, magnesium glutamate, magnesium benzoate, magnesium stearate, magnesium acrylate, magnesium methacrylate, magnesium gluconate, magnesium naphthenate, magnesium salicylate, magnesium lactate, magnesium monoperoxyphthalate, and the like. These magnesium compounds may be used alone or in combination of two or more. Among these, magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium acetate, magnesium nitrate, or magnesium sulfate is preferred, and magnesium oxide, magnesium hydroxide, magnesium nitrate, or magnesium acetate is more preferred.
[0038] The average particle size of the magnesium compound is not particularly limited, but is preferably 1 μm or more and 10 μm or less, more preferably 1.5 μm or more and 5 μm or less, even more preferably 2 μm or more and 4 μm or less, and particularly preferably 2.5 μm or more and 3.5 μm or more. When the average particle size of the magnesium compound is equal to or more than the lower limit, particle aggregation during spinel crystallization can be more effectively prevented. On the other hand, when the average particle size of the magnesium compound is equal to or less than the upper limit, spinel crystallization can progress more efficiently to the center of the particle.
[0039] The magnesium compound may be a commercially available product or may be prepared by oneself. When preparing magnesium compounds by oneself, the reactivity can be adjusted. For example, magnesium hydroxide with a small particle size can be obtained by neutralizing an acidic aqueous solution of magnesium ions with a base. The resulting magnesium hydroxide with a small particle size has high reactivity, so the crystallite size of the spinel obtained using it tends to be large.
[0040] [Aluminum compounds] The aluminum compound is not particularly limited, but examples thereof include aluminum metal, aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, aluminum oxide, etc. Examples of aluminum oxide include aluminum oxide hydrate, β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, θ-aluminum oxide, α-aluminum oxide, mixed aluminum oxide having two or more crystal phases, etc.
[0041] The above-mentioned aluminum compound is preferably aluminum oxide, and is preferably aluminum oxide having at least one crystal form selected from the group consisting of α-crystals, β-crystals, γ-crystals, δ-crystals, and θ-crystals, and is more preferably aluminum oxide having α-crystals.
[0042] In addition, the above-mentioned aluminum compound preferably contains molybdenum. In this case, the molybdenum-containing form of the aluminum compound containing molybdenum is not particularly limited, but may be, as with spinel particles, a form in which molybdenum is attached to, coated on, bonded to, or disposed in other similar forms on the surface of the aluminum compound, a form in which molybdenum is incorporated into the aluminum compound, or a combination thereof. In this case, examples of the "form in which molybdenum is incorporated into the aluminum compound" include a form in which at least a part of the atoms constituting the aluminum compound is replaced with molybdenum, and a form in which molybdenum is disposed in a space (including a space caused by defects in the crystal structure) that may exist inside the crystal of the aluminum compound. In the form of substitution, the atom constituting the aluminum compound to be substituted is not particularly limited, and may be any of an aluminum atom, an oxygen atom, and other atoms.
[0043] Of the above aluminum compounds, it is preferable to use an aluminum compound containing molybdenum, and it is more preferable to use an aluminum compound into which molybdenum is incorporated.
[0044] The reason why aluminum compounds containing molybdenum are preferred is not necessarily clear, but is presumed to be due to the following mechanism. That is, it is considered that the molybdenum contained in the aluminum compound functions to promote nucleation at the solid-phase interface and promote solid-phase diffusion of aluminum atoms and magnesium atoms, and the solid-phase reaction between the aluminum compound and the magnesium compound proceeds more favorably. That is, as described below, aluminum compounds containing molybdenum can function as both an aluminum compound and molybdenum. In particular, aluminum compounds incorporating molybdenum have molybdenum located directly or in the vicinity of the reaction point, and can more effectively exert the effect of molybdenum. Note that the above mechanism is merely speculation, and even if the desired effect is obtained by a mechanism different from the above mechanism, it is still within the technical scope.
[0045] The shape of the aluminum compound is not particularly limited, and examples thereof include polyhedral, spherical, elliptical, cylindrical, polygonal columnar, needle-like, rod-like, plate-like, disk-like, thin plate-like, scale-like, etc. Among these, plate-like shapes are preferred, since, as will be described later, in the production method according to the embodiment, spinel particles that reflect the shape of the aluminum compound tend to be obtained.
[0046] The average particle size of the aluminum compound is not particularly limited, but is appropriately adjusted according to the particle size of the plate-like spinel to be obtained. The average particle size of the aluminum compound is 0.1 μm or more and 500 μm or less, preferably 0.3 μm or more and 100 μm or less, more preferably 0.5 μm or more and 50 μm or less, even more preferably 1 μm or more and 30 μm or less, even more preferably 1 μm or more and 20 μm or less, particularly preferably 1 μm or more and 10 μm or less, and most preferably 3.8 μm or more and 7.0 μm or less. If the average particle size of the aluminum compound is the above lower limit or more, particle aggregation during spinel crystallization can be more effectively prevented. On the other hand, if the average particle size of the aluminum compound is the above upper limit or less, spinel crystallization can proceed more efficiently to the center of the particle.
[0047] The thickness of the aluminum compound is from 0.01 μm to 5 μm, preferably from 0.05 μm to 3 μm, more preferably from 0.1 μm to 1 μm, even more preferably from 0.15 μm to 0.75 μm, and particularly preferably from 0.2 μm to 0.5 μm. By keeping the thickness of the aluminum compound within the above range, it is possible to obtain plate-like spinel particles having a larger aspect ratio.
[0048] The aspect ratio of the aluminum compound is from 3 to 500, preferably from 5 to 100, more preferably from 7 to 50, even more preferably from 9 to 30, and particularly preferably from 10 to 25. When the aspect ratio is equal to or more than the above lower limit, plate-like spinel particles having better mechanical strength can be obtained, while when the aspect ratio is equal to or less than the above upper limit, the plate-like spinel particles can provide molded articles and coating films having smoother surfaces.
[0049] The aluminum compound may be a commercially available product or may be prepared by oneself. When preparing the aluminum compound by oneself, for example, an aluminum compound containing molybdenum can be prepared by a flux method described in detail below. That is, in a preferred embodiment, the method for producing spinel particles further includes a step of preparing the aluminum compound by a flux method.
[0050] The flux method is different from the solid-phase method described above and is classified as a liquid-phase method, especially a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). The solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).
[0051] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form euhedral polyhedral crystals.
[0052] When preparing an aluminum compound by a flux method, if a molybdenum compound is used as a fluxing agent, an aluminum compound containing molybdenum can be obtained via an intermediate compound, aluminum molybdate. In this case, the molybdenum contained in the aluminum compound can be considered as a flux impurity, which is said to be a disadvantage of the flux method, but as described above, in one embodiment of the present invention, the molybdenum contained in the aluminum compound can exert a suitable effect when producing plate-like spinel particles.
[0053] (Flux evaporation method) In one embodiment, the flux method includes a flux evaporation step of calcining a mixture containing an aluminum source and a molybdenum compound, and a cooling step of cooling the aluminum compound crystal-grown in the calcination step.
[0054] Aluminum Source The aluminum source is not particularly limited, but may be aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina, alumina hydrate, α-alumina, mixed alumina having two or more crystal phases, etc. Examples of transition alumina include γ-alumina, δ-alumina, θ-alumina, etc. The above aluminum sources may be used alone or in combination of two or more. Among them, aluminum hydroxide, transition alumina, boehmite, pseudo-boehmite, or alumina hydrate is preferred, and aluminum hydroxide, transition alumina, or boehmite is more preferred.
[0055] The aluminum source may be commercially available or may be self-prepared. When preparing the aluminum source by oneself, for example, an alumina hydrate or transition alumina having high structural stability at high temperatures can be prepared by neutralizing an aqueous solution of aluminum. More specifically, the alumina hydrate can be prepared by neutralizing an acidic aqueous solution of aluminum with a base, and the transition alumina can be prepared by heat-treating the alumina hydrate obtained above. Note that the alumina hydrate or transition alumina obtained in this manner has high structural stability at high temperatures, and therefore when calcined in the presence of molybdenum, an aluminum compound containing molybdenum having a large average particle size tends to be obtained.
[0056] In the above-mentioned flux method, the shape of the aluminum source is not particularly limited, and any of a sphere, an amorphous shape, an aspected structure, a sheet, etc. can be suitably used. As the aspected structure, for example, a shape of a wire, a fiber, a ribbon, a tube, etc. can also be suitably used.
[0057] Similarly, in the above-mentioned flux method, the particle size of the aluminum source is not particularly limited, and a solid aluminum compound having a particle size of several nm to several hundred μm can be suitably used.
[0058] The aluminum source may also form a complex with an organic compound. Examples of the complex include an organic-inorganic complex obtained by modifying an aluminum compound with an organic silane, an aluminum compound complex adsorbed with a polymer, and a complex coated with an organic compound. When using these complexes, the content of the organic compound is not particularly limited, but is preferably 60% by mass or less, and more preferably 30% by mass or less.
[0059] The specific surface area of the aluminum source is not particularly limited. Since the molybdenum compound acts effectively, the larger the specific surface area, the more preferable it is. However, by adjusting the firing conditions and the amount of the molybdenum compound used, any specific surface area can be used as the raw material.
[0060] In the above-mentioned flux method, a shape control agent can be used to form an aluminum compound. The shape control agent plays an important role in the growth of plate-like crystals of alumina by calcining an aluminum source in the presence of a molybdenum compound.
[0061] The state in which the shape-controlling agent is present is not particularly limited, and for example, a physical mixture of the shape-controlling agent and an aluminum compound, or a complex in which the shape-controlling agent is present uniformly or locally on the surface or inside of the aluminum source, can be suitably used.
[0062] The shape control agent may be added to the aluminum compound, or may be contained in the aluminum compound as an impurity.
[0063] Shape control agents play an important role in the growth of plate-like crystals. In the commonly used molybdenum oxide flux method, molybdenum oxide selectively adsorbs to the (113) plane of the α crystals of alumina, making it difficult for crystal components to be supplied to the (113) plane, and completely suppressing the appearance of the (001) or (006) planes, forming polyhedral particles based on a hexagonal bipyramidal shape. In the above-mentioned flux method, a shape control agent is used to suppress the selective adsorption of crystal components to the (113) plane by the flux agent molybdenum oxide, thereby forming a plate-like shape with a close-packed hexagonal lattice crystal structure that is the most thermodynamically stable with a well-developed (001) plane. By using a molybdenum compound as a flux agent, it is possible to more easily form plate-like alumina particles containing molybdenum with a high α crystallization rate.
[0064] As for the type of shape control agent, silicon or a silicon compound containing silicon element, germanium or a germanium compound containing germanium element can be used. It is preferable to use silicon or a silicon compound containing silicon element, because it is possible to produce plate-like alumina particles at a lower cost and with excellent productivity. By using silicon or a silicon compound as a shape control agent, an aluminum compound having a high aspect ratio can be easily produced.
[0065] The silicon or silicon compound containing silicon element is not particularly limited, and known compounds can be used. The silicon or silicon compound containing silicon element may be an artificially synthesized silicon compound or a natural silicon compound. Examples of the artificially synthesized silicon compound include metal silicon, organosilane, silicon resin, silica fine particles, silica gel, mesoporous silica, SiC, and mullite. Examples of the natural silicon compound include biosilica. Among them, it is preferable to use organosilane, silicon resin, or silica fine particles from the viewpoint of forming a more uniform composite or mixture with an aluminum compound. The silicon compound containing silicon or silicon element may be used alone or in combination of two or more.
[0066] The shape of silicon or silicon compound containing silicon element is not particularly limited, and for example, a sphere, an amorphous, an aspected structure, a sheet, etc. can be suitably used. As the aspected structure, for example, a shape of a wire, a fiber, a ribbon, a tube, etc. can also be suitably used.
[0067] The silicon content, calculated as silicon dioxide, is preferably 10% by mass or less, more preferably 0.001% by mass or more and 5% by mass or less, even more preferably 0.01% by mass or more and 4% by mass or less, and particularly preferably 0.6% by mass or more and 2.5% by mass or less, relative to 100% by mass of the aluminum compound. The silicon content can be determined by XRF analysis.
[0068] Molybdenum compounds The molybdenum compound is not particularly limited, but may be metal molybdenum, molybdenum oxide, molybdenum sulfide, sodium molybdate, potassium molybdate, calcium molybdate, ammonium molybdate, H3PMo 12 O 40 , H3SiMo 12 O 40etc. In this case, the molybdenum compound includes isomers. For example, molybdenum oxide may be molybdenum dioxide (IV) (MoO2) or molybdenum trioxide (VI) (MoO3). The above-mentioned molybdenum compounds may be used alone or in combination of two or more. Among these, molybdenum trioxide, molybdenum dioxide, or ammonium molybdate is preferable, and molybdenum trioxide is more preferable.
[0069] The molar ratio of the molybdenum element of the molybdenum compound to the aluminum element of the aluminum compound (molybdenum element / aluminum element) is preferably 0.01 to 3.0, more preferably 0.03 to 1.0. When the molar ratio is equal to or greater than the lower limit, the crystal growth of the molybdenum-containing aluminum compound can proceed more favorably. On the other hand, when the molar ratio is equal to or less than the upper limit, the preparation of the molybdenum-containing aluminum compound can be industrially more efficiently.
[0070] -Flux evaporation process- By calcining a mixture containing an aluminum source and a molybdenum compound, an intermediate compound, aluminum molybdate, is produced, and the aluminum molybdate is decomposed and the molybdenum compound is evaporated, thereby producing an aluminum compound containing molybdenum. At this time, the evaporation of the molybdenum compound serves as a driving force for the crystal growth of the aluminum compound containing molybdenum.
[0071] The firing temperature is not particularly limited, but is preferably 700°C to 2000°C, more preferably 900°C to 1600°C, even more preferably 950°C to 1500°C, and particularly preferably 1000°C to 1400°C. If the firing temperature is equal to or higher than the lower limit, the flux reaction proceeds more efficiently. On the other hand, if the firing temperature is equal to or lower than the upper limit, the load on the firing furnace and fuel costs can be further reduced.
[0072] The state of the aluminum source and the molybdenum compound during firing is not particularly limited, and it is sufficient that the molybdenum compound and the aluminum source are present in the same space. For example, even if the two are not mixed, the flux reaction can proceed. When mixing the two, simple mixing of powders, mechanical mixing using a grinder, mixing using a mortar, etc. can be performed, and in this case, the resulting mixture may be in either a dry state or a wet state.
[0073] The firing time is not particularly limited, but is preferably from 5 minutes to 30 hours, and more preferably from 10 minutes to 15 hours from the viewpoint of efficiently forming the molybdenum-containing aluminum compound.
[0074] The firing atmosphere is not particularly limited, but is preferably, for example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen or argon, more preferably a non-corrosive oxygen-containing atmosphere or nitrogen atmosphere from the viewpoint of the safety of the operator and the durability of the furnace, and further preferably an air atmosphere from the viewpoint of cost.
[0075] The calcination apparatus is not particularly limited, and a so-called calcination furnace is usually used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum compound, and more preferably is a highly airtight calcination furnace that can efficiently utilize the molybdenum compound.
[0076] -Cooling process- The cooling step is a step of cooling the aluminum compound whose crystals have grown in the firing step.
[0077] The cooling rate is not particularly limited, but is preferably 1°C / hour to 1000°C / hour, more preferably 5°C / hour to 500°C / hour, and even more preferably 50°C / hour to 100°C / hour. If the cooling rate is equal to or higher than the lower limit, the manufacturing time can be further shortened. On the other hand, if the cooling rate is equal to or lower than the upper limit, the firing container is less likely to crack due to heat shock and can be used for a longer period of time, which is preferable.
[0078] The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.
[0079] -Molybdenum-containing aluminum compounds- The aluminum compounds obtained by the flux method are usually colored because they contain molybdenum. The color of the color varies depending on the amount of molybdenum contained, but is usually light blue to dark blue close to black, and the color tends to become darker in proportion to the molybdenum content. Depending on the composition of the aluminum compound containing molybdenum, it may be colored in other colors. For example, if the compound containing molybdenum contains chromium, it may be red, and if it contains nickel, it may be yellow.
[0080] The molybdenum content of the aluminum compound containing molybdenum is not particularly limited, but is preferably 0.1% by mass or more and 1% by mass or less, more preferably 0.2% by mass or more and 0.9% by mass or less, even more preferably 0.3% by mass or more and 0.9% by mass or less, even more preferably 0.5% by mass or more and 0.88% by mass or less, particularly preferably 0.7% by mass or more and 0.87% by mass or less, and most preferably 0.83% by mass or more and 0.86% by mass or less, in terms of molybdenum trioxide. When the molybdenum content is equal to or more than the lower limit, the crystal growth of the spinel can proceed more efficiently. On the other hand, when the molybdenum content is equal to or less than the upper limit, the crystal quality of the aluminum compound can be improved, which is preferable. In this specification, the molybdenum content in the aluminum compound can be measured using the same method as that described for the molybdenum content in the plate-like spinel particles.
[0081] In the aluminum compound containing molybdenum, molybdenum acts as a fluxing agent, and it is preferable that the molybdenum acts as a fluxing agent, and that the molybdenum has a high alpha crystallization rate with a crystal plane other than the (001) plane as the main crystal plane, and it is more preferable that the alpha crystallization rate is 90% or more.
[0082] (slow cooling method) In one embodiment, the flux method includes a step of firing a mixture containing an aluminum source and a molybdenum compound, and a step of cooling the resulting fired product to cause crystal growth.
[0083] [molybdenum] Molybdenum has functions such as promoting nucleation at the interface in solid-phase reactions and promoting solid-phase diffusion of at least one of magnesium atoms and aluminum atoms.
[0084] Molybdenum can be used in the form of molybdenum metal or a compound containing molybdenum. Specific examples of compounds containing molybdenum include the above-mentioned molybdenum compounds and aluminum compounds containing molybdenum. The aluminum compounds containing molybdenum can be used as compounds containing molybdenum and aluminum compounds. The above-mentioned molybdenum can be used alone or in combination of two or more kinds.
[0085] The molybdenum content is preferably in the range of 0.00001 to 0.05, more preferably 0.0001 to 0.03, in terms of the molar ratio of molybdenum to aluminum in the aluminum compound (molybdenum / aluminum). When the molar ratio is within the above range, the formation of a solid solution between the magnesium compound and the aluminum compound and the crystallization of spinel can proceed more efficiently.
[0086] <Firing process> The calcination step comprises calcining a magnesium compound and an aluminum compound in the presence of molybdenum. This is a step in which crystals are grown into the plate-like spinel particles by solution formation and crystallization.
[0087] The solid solution and crystallization are usually performed by the so-called solid phase method. The mechanism of solid solution and crystallization in the solid phase method is presumed to be as follows. That is, when heating is performed in an environment where the magnesium compound and the aluminum compound are in contact with each other, the magnesium compound and the aluminum compound form nuclei at the interface (solid-phase interface), thereby strengthening the bond between the solid phases. Then, the solid phase reaction can proceed with the formed nuclei as a carrier. In this case, the solid phase reaction can utilize the fact that the binary phase diagram of the magnesium compound and the aluminum compound is of a eutectic type, and therefore the temperature at which the magnesium compound and the aluminum compound can react at the interface is lower than the temperature at which the magnesium compound or the aluminum compound melts alone. Specifically, the magnesium compound and the aluminum compound react at the interface to form nuclei, and at least one of the magnesium atoms and the aluminum atoms diffuses in the solid phase through the nuclei and reacts with at least one of the aluminum compound and the magnesium atoms. This makes it possible to obtain dense crystals, i.e., spinel particles. In this case, in the solid-phase diffusion, the diffusion rate of magnesium atoms into the aluminum compound is relatively higher than the diffusion rate of aluminum atoms into the magnesium compound, so that spinel particles reflecting the shape of the aluminum compound tend to be obtained. Therefore, by appropriately changing the shape and average particle size of the aluminum compound, it may be possible to control the shape and average particle size of the spinel particles. In the manufacturing method according to the embodiment, by using plate-like alumina particles containing molybdenum as the aluminum compound, plate-like spinel particles can be manufactured more easily.
[0088] Here, the above-mentioned solid-phase reaction is carried out in the presence of molybdenum. The action of molybdenum is not necessarily clear, but it is believed that the solid-phase reaction proceeds more favorably, for example, by promoting nucleation at the interface and promoting solid-phase diffusion of at least one of magnesium atoms and aluminum atoms. As explained in the above-mentioned flux method, it is presumed that the reaction process includes a process in which molybdenum first reacts with an aluminum compound to form an intermediate aluminum molybdate, and then the aluminum molybdate reacts with a magnesium compound. In spinel particles having multiple metal components, defective structures and the like are likely to occur during the firing process, making it difficult to precisely control the crystal structure, but the crystal structure of the spinel crystal can be controlled by using molybdenum. This increases the crystallite size of the (311) plane, and plate-like spinel particles with excellent thermal conductivity can be obtained. In addition, since the solid-phase reaction is carried out in the presence of molybdenum, the obtained plate-like spinel particles may contain molybdenum.
[0089] The crystallization control of the (311) plane of the spinel particles, such as the crystallite size, can be performed by changing the amount of molybdenum used, the type of magnesium compound, the firing temperature, the firing time, and the mixed state of the magnesium compound and the aluminum compound. The reason for this is that the amount of molybdenum, the type of magnesium compound, the firing temperature, the firing time, and the mixed state of the magnesium compound and the aluminum compound are related to the rate of dissolution and crystallization of the magnesium compound and the aluminum compound in the solid-phase reaction. The use of a highly reactive magnesium compound can increase the rate of dissolution and crystallization of the magnesium compound, while the increase in the amount of molybdenum used, high-temperature firing, and long-term firing can increase the rate of dissolution and crystallization of at least one of the magnesium atoms and the aluminum atoms, respectively, and for example, the crystallite size of the (311) plane can be increased.
[0090] The firing temperature is not particularly limited, but is preferably less than 1300° C., more preferably 800° C. or more and less than 1300° C., and even more preferably 900° C. or more and 1200° C. or less. By keeping the firing temperature at or below the upper limit, plate-like spinel particles can be produced more efficiently in a shorter time. On the other hand, by keeping the firing temperature at or below the upper limit, the shape and dispersibility of the spinel particles can be more easily controlled.
[0091] The firing time is not particularly limited, but is preferably 0.1 to 1000 hours, more preferably 3 to 100 hours. If the firing time is equal to or more than the lower limit, plate-like spinel particles having a larger crystallite size of the (311) plane can be obtained. On the other hand, if the firing time is equal to or less than the upper limit, the production cost can be lowered.
[0092] In the firing, a shape control agent can be used to promote the formation of a solid solution and crystallization of the magnesium compound and the aluminum compound, and to control the shape. Examples of the shape control agent include sodium compounds and potassium compounds. By adding a shape control agent, molybdenum is efficiently diffused, contributing to homogenization of crystal formation, and plate-like spinel particles having a more uniform shape and particle surface and high smoothness can be obtained.
[0093] The sodium compound is not particularly limited, but includes sodium, sodium chloride, sodium chlorite, sodium chlorate, sodium sulfate, sodium hydrogen sulfate, sodium sulfite, sodium hydrogen sulfite, sodium nitrate, sodium carbonate, sodium hydrogen carbonate, sodium acetate, sodium oxide, sodium bromide, sodium bromate, sodium hydroxide, sodium silicate, sodium phosphate, sodium hydrogen phosphate, sodium sulfide, sodium hydrogen sulfide, sodium molybdate, sodium tungstate, and the like. In this case, the sodium compound includes isomers, as in the case of the molybdenum compound. Among them, it is preferable to use sodium carbonate, sodium hydrogen carbonate, sodium oxide, sodium hydroxide, sodium chloride, sodium sulfate, or sodium molybdate, and it is more preferable to use sodium carbonate, sodium hydrogen carbonate, sodium chloride, sodium sulfate, or sodium molybdate. The above-mentioned sodium compounds may be used alone or in combination of two or more kinds. In addition, since sodium molybdate contains molybdenum, it can also function as the above-mentioned molybdenum compound.
[0094] The potassium compound is not particularly limited, and examples thereof include potassium, potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, and potassium tungstate. In this case, the potassium compound contains isomers, as in the case of the molybdenum compound. Among them, it is preferable to use potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, or potassium molybdate, and it is more preferable to use potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, or potassium molybdate. The above potassium compounds may be used alone or in combination of two or more. In addition, potassium molybdate contains molybdenum, so it can also function as the above molybdenum compound.
[0095] The amount of the shape control agent added is preferably 20% by mass or more and 90% by mass or less, more preferably 30% by mass or more and 80% by mass or less, even more preferably 40% by mass or more and 70% by mass or less, even more preferably 50% by mass or more and 68% by mass or less, particularly preferably 55% by mass or more and 67% by mass or less, and most preferably 61% by mass or more and 66% by mass or less, in terms of oxide, relative to 100% by mass of the raw material. By keeping the amount of the shape control agent added within the above range, plate-like spinel particles with excellent surface smoothness can be obtained. In addition, the aspect ratio can be made larger, and the mechanical strength tends to be superior. These additives are preferably mixed in the above-mentioned mixing step before firing.
[0096] The firing atmosphere may be an air atmosphere, an inert gas atmosphere such as nitrogen gas or argon gas, an oxygen atmosphere, an ammonia gas atmosphere, or a carbon dioxide atmosphere. In this case, an air atmosphere is preferable from the viewpoint of production costs.
[0097] The pressure during firing is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure. From the viewpoint of efficiently discharging molybdenum oxide vapor generated during firing from the firing furnace, firing is preferably performed under reduced pressure.
[0098] The heating means is not particularly limited, but it is preferable to use a calcination furnace. Examples of the calcination furnace that can be used in this case include a tunnel furnace, a roller hearth furnace, a rotary kiln, and a muffle furnace. The firing furnace is preferably made of a material that does not react with molybdenum oxide vapor, and it is more preferable to use a firing furnace that is highly airtight.
[0099] <Cooling process> The production method of the present invention may include a cooling step, which is a step of cooling the spinel particles that have undergone crystal growth in the firing step.
[0100] The cooling rate is not particularly limited, but is preferably 1°C / hour to 1000°C / hour, more preferably 5°C / hour to 500°C / hour, and even more preferably 50°C / hour to 100°C / hour. If the cooling rate is equal to or higher than the lower limit, the manufacturing time can be further shortened. On the other hand, if the cooling rate is equal to or lower than the upper limit, the firing container is less likely to crack due to heat shock and can be used for a longer period of time.
[0101] The cooling method is not particularly limited, and may be natural cooling or may use a cooling device.
[0102] [Post-processing process] The manufacturing method of the present invention may include a post-treatment step. The post-treatment step is a step of removing additives and the like. The post-treatment step may be carried out after the above-mentioned firing step, after the above-mentioned cooling step, or after the firing step and the cooling step. Moreover, the post-treatment step may be repeated two or more times as necessary. Post-treatment methods include washing and high temperature treatment, which may be performed in combination. The washing method is not particularly limited, but for example, the metal oxide can be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, an acidic aqueous solution, or the like. In this case, the molybdenum content can be controlled by appropriately changing the concentrations and amounts of water, ammonia aqueous solution, sodium hydroxide aqueous solution, and acidic aqueous solution used, as well as the washing locations and washing times. As a method of high temperature treatment, a method of raising the temperature to the sublimation point or boiling point of the additive or higher can be mentioned.
[0103] [Crushing process] In the fired product, the tabular spinel particles may aggregate and not satisfy the particle size range suitable for the present invention, so the tabular spinel particles may be pulverized as necessary to satisfy the particle size range suitable for the present invention. The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.
[0104] [Classification process] The plate-like spinel particles are preferably classified to adjust the average particle size and improve the powder flowability, or to suppress an increase in viscosity when the particles are mixed with a binder to form a matrix. "Classification" refers to an operation of classifying particles into groups based on their size. The classification may be either wet or dry, but from the viewpoint of productivity, dry classification is preferred. Dry classification includes classification by sieving, as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag, but from the viewpoint of classification accuracy, wind classification is preferred, and can be performed using a classifier such as an air classifier utilizing the Coanda effect, a swirling air classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier. The above-mentioned pulverization step and classification step can be carried out at any stage required, including before or after the organic compound layer forming step described below. Depending on whether or not pulverization or classification is performed and the selection of the conditions therefor, for example, it is possible to adjust the average particle size of the obtained plate-like spinel particles.
[0105] The tabular spinel particles according to the embodiment, or the tabular spinel particles obtained by the production method according to the embodiment, are preferably those with little or no aggregation, because they are more likely to exhibit their inherent properties, are more easily handled, and have better dispersibility when dispersed in a dispersion medium. In the production method of the tabular spinel particles, if the above-mentioned grinding step or classification step is not performed and those with little or no aggregation are obtained, there is no need to perform the steps, and the tabular spinel particles having the desired excellent properties can be produced with high productivity, which is preferable. EXAMPLES
[0106] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0107] <Synthesis of raw material α-alumina particles> <Synthesis Example 1> Synthesis of α-alumina particles A-1 A mixture was obtained by mixing 145.3 g of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd., average particle size 12 μm), 1.90 g of silicon dioxide (manufactured by Kanto Chemical Co., Ltd., special grade), and 5 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.) in a mortar. The mixture obtained was placed in a crucible, heated to 1100°C at 5°C / min in a ceramic electric furnace, and fired at 1100°C for 10 hours. The temperature was then lowered to room temperature at 5°C / min, and the crucible was removed to obtain 99 g of light blue powder. The powder obtained was crushed in a mortar until it passed through a 106 μm sieve. Next, 98 g of the obtained light blue powder was dispersed in 150 mL of 0.5% ammonia water, and the dispersion solution was stirred at room temperature (25 to 30°C) for 0.5 hours, after which the ammonia water was removed by filtration, and the molybdenum remaining on the particle surface was removed by washing with water and drying, to obtain 96 g of white powder. The obtained powder had an average particle size of 7.0 μm as determined by a laser diffraction particle size distribution analyzer, and was confirmed to have a polygonal plate shape, with very few aggregates, and to be a plate-shaped particle with excellent handleability by SEM observation. Furthermore, when XRD measurement was performed, a sharp peak scattering due to α-alumina appeared, and no alumina crystal peaks other than the α crystal structure were observed, confirming that it was a plate-shaped alumina with a dense crystal structure. In addition, the α conversion rate was 90% or more. Furthermore, from the results of fluorescent X-ray quantitative analysis, it was confirmed that the obtained particles contained 0.83 mass% molybdenum in terms of molybdenum trioxide. Furthermore, the density was measured and found to be 3.95 g / cm 3 It was.
[0108] <Synthesis Example 2> Synthesis of α-alumina particles A-2 The same operation as in Synthesis Example 1 was performed to obtain 98 g of a light blue powder, except that 145.3 g of aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd., average particle size 2 μm), 2.85 g of silicon dioxide, and 5 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.) were mixed in a mortar. The obtained powder had an average particle size of 3.8 μm as determined by a laser diffraction particle size distribution analyzer, and was confirmed to have a polygonal plate shape, extremely few aggregates, and plate-shaped particles with excellent handleability by SEM observation. Furthermore, when XRD measurement was performed, a sharp peak scattering due to α-alumina appeared, and no alumina crystal peaks other than the α crystal structure were observed, confirming that it was plate-shaped alumina with a dense crystal structure. In addition, the α conversion rate was 90% or more. Furthermore, the results of fluorescent X-ray quantitative analysis confirmed that the obtained particles contained 0.86 mass% molybdenum in terms of molybdenum trioxide. Furthermore, the density was measured and found to be 3.94 g / cm 3 It was.
[0109] <Synthesis of spinel particles> <Example 1> Synthesis of spinel particles S-a1 20 g of the α-alumina particles A-1 obtained in Synthesis Example 1 and 7.86 g of magnesium oxide (Kanjima Chemical Co., Ltd., average particle size 3.5 μm) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible, heated to 1050° C. at 5° C. / min in a ceramic electric furnace, and held at 1050° C. for 10 hours for firing. After that, the temperature was lowered to room temperature at 5° C. / min, and the crucible was removed to obtain 27.5 g of white powder. The obtained powder was crushed in a mortar until it passed through a 150 μm sieve. Next, 25 g of the obtained white powder was mixed with 100 mL of 2% nitric acid, alumina beads with a diameter of 5 mm were added, and the mixture was crushed by 20 degrees in a paint conditioner. After that, the dispersion solution was filtered to remove the 2% nitric acid, and the molybdenum remaining on the particle surface was removed by washing with water and drying, and 24.5 g of white powder was obtained. The obtained powder was confirmed to be plate-shaped, with very few aggregates, and to be particles with excellent handleability by SEM observation (see Figure 1 (A)). Furthermore, when XRD measurement was performed, a sharp peak scattering due to spinel was observed. In addition, the crystallite diameter was determined from the peak of the (311) plane observed around 37 degrees using a CALSA detector, and it was confirmed to be 72 nm. Furthermore, from the results of fluorescent X-ray quantitative analysis, it was confirmed that the obtained particles contained 0.44 mass% of molybdenum in terms of molybdenum trioxide.
[0110] Example 2: Synthesis of spinel particles S-a2 The mixture obtained was placed in a crucible, heated to 1150°C at 5°C / min in a ceramic electric furnace, and held at 1150°C for 10 hours for firing. The same operation as in Example 1 was performed to obtain 24.5g of white powder. The obtained powder was confirmed to be plate-shaped, with very few aggregates, and to be particles with excellent handleability by SEM observation (see FIG. 1(B)). Furthermore, when XRD measurement was performed, sharp peak scattering due to spinel was observed. In addition, the crystallite size was determined from the peak of the (311) plane observed at around 37°C using a CALSA detector, and was 82nm. It was confirmed that firing at a high temperature is significant for crystal growth compared to the firing at 1050°C in Example 1. Furthermore, it was confirmed from the results of fluorescent X-ray quantitative analysis that the obtained particles contained 0.48% by mass of molybdenum in terms of molybdenum trioxide.
[0111] Example 3: Synthesis of spinel particles S-a3 20 g of α-alumina particles A-2 obtained in Synthesis Example 2 and 7.86 g of magnesium oxide (Kanjima Chemical Co., Ltd., average particle size 3.5 μm) were mixed in a mortar to obtain a mixture, and the same operation as in Example 1 was performed to obtain 24.6 g of white powder. The average particle size of the obtained powder was 4.0 μm. When the α-alumina particles A-2 obtained in Synthesis Example 2, which had an average particle size of 3.8 μm smaller than that of the α-alumina particles A-1 obtained in Synthesis Example 1, were used, particles with an average particle size smaller than that of the plate-like spinel particles S-a1 obtained in Example 1 were obtained. In addition, it was confirmed by SEM observation (see FIG. 1(C)) that the particles were plate-like, had very few aggregates, and had excellent handleability. Furthermore, when XRD measurement was performed, a sharp peak scattering derived from the spinel was observed. In addition, the crystallite size was determined from the peak of the (311) plane observed around 37 degrees using a CALSA detector, and was confirmed to be 70 nm. Furthermore, the results of fluorescent X-ray quantitative analysis confirmed that the particles contained 0.53 mass % of molybdenum, calculated as molybdenum trioxide.
[0112] Example 4: Synthesis of spinel particles S-a4 The same operation as in Example 1 was performed except that 20 g of α-alumina particles A-1 obtained in Synthesis Example 1, 7.86 g of magnesium oxide (Kanjima Chemical Co., Ltd., average particle size 3.5 μm), and 1.67 g of molybdenum trioxide were mixed in a mortar to obtain a mixture, and 24.6 g of white powder was obtained. The obtained powder was confirmed to be plate-shaped, with very few aggregates, and to be particles with excellent handleability by SEM observation (see FIG. 1(D)). Furthermore, when XRD measurement was performed, sharp peak scattering due to spinel was observed. In addition, the crystallite diameter was calculated using a CALSA detector from the peak of the (311) plane observed around 37 degrees, and was 88 nm, which was larger than the crystallite diameter of the compound in Example 2 that was fired without adding molybdenum trioxide, and it was confirmed that molybdenum trioxide contributed to crystal growth. Furthermore, the results of fluorescent X-ray quantitative analysis confirmed that the obtained particles contained 0.61 mass % of molybdenum in terms of molybdenum trioxide.
[0113] <Example 5> Synthesis of spinel particles S-a5 20 g of α-alumina particles A-1 obtained in Synthesis Example 1, 7.86 g of magnesium oxide (Kanjima Chemical Co., Ltd., average particle size 3.5 μm), and 83.57 g of sodium chloride were mixed in a mortar to obtain a mixture, and the same operation as in Example 1 was performed to obtain 24.5 g of white powder. The average particle size of the obtained powder was 8.3 μm, and by adding sodium chloride, particles with an average particle size larger than that of the plate-like spinel particles S-a2 obtained in Example 2 were obtained. Furthermore, when XRD measurement was performed, sharp peak scattering due to spinel was observed. In addition, the crystallite size was determined from the peak of the (311) plane observed around 37 degrees using a CALSA detector, and it was confirmed to be 66 nm. Furthermore, from the results of fluorescent X-ray quantitative analysis, it was confirmed that the obtained particles contained 0.31 mass % of molybdenum in terms of molybdenum trioxide.
[0114] <Example 6> Synthesis of spinel particles S-a6 20 g of α-alumina particles A-1 obtained in Synthesis Example 1, 7.86 g of magnesium oxide (Kamishima Chemical Co., Ltd., average particle size 3.5 μm), and 83.57 g of sodium chloride were mixed in a mortar to obtain a mixture, and the same operation as in Example 1 was performed to obtain 24.5 g of white powder. The average particle size of the obtained powder was 8.0 μm, and by adding potassium chloride in the same manner as in Example 5, particles with a larger average particle size than the plate-like spinel particles S-a2 obtained in Example 2 were obtained. Furthermore, when XRD measurement was performed, sharp peak scattering due to spinel was observed. In addition, the crystallite size was determined from the peak of the (311) plane observed around 37 degrees using a CALSA detector, and it was confirmed to be 68 nm. Furthermore, from the results of fluorescent X-ray quantitative analysis, it was confirmed that the obtained particles contained 0.33 mass % of molybdenum in terms of molybdenum trioxide.
[0115] <Comparative Example 1> Synthesis of spinel particles S-b1 23.53 g of commercially available boehmite (particle diameter 2 μm) and 7.86 g of magnesium oxide (Kamishima Chemical Co., Ltd., average particle diameter 3.5 μm) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible, heated to 1150 ° C. at 5 ° C. / min in a ceramic electric furnace, and fired at 1150 ° C. for 10 hours. After that, the temperature was lowered to room temperature at 5 ° C. / min, and the crucible was removed to obtain 27.6 g of white powder. The obtained powder was crushed in a mortar until it passed through a 150 μm sieve. Next, 25 g of the obtained white powder was mixed with 100 mL of 2% nitric acid, alumina beads with a diameter of 5 mm were added, and the mixture was crushed for 20 minutes in a paint conditioner. After that, the dispersion solution was filtered to remove the 2% nitric acid, washed with water and dried, and 24.6 g of white powder was obtained. Observation of the obtained powder with SEM (see FIG. 1(E)) showed that it was plate-like, but the particle shape and particle size were not uniform. The average thickness of the plate was 1 μm, the average particle size determined by a laser diffraction particle size distribution analyzer was 2.9 μm, and the aspect ratio determined by the average particle size / average thickness was 2.9, which was an extremely small value compared to the aspect ratio of the plate-like spinel particles obtained in Examples 1 to 6. Furthermore, when an XRD measurement was performed, peak scattering due to spinel was observed, but the peak was broad compared to the measurement results of the plate-like spinel particles obtained in Examples 1 to 6, and the crystallite size was calculated from the peak of the (311) plane observed at around 37 degrees using a CALSA detector, and was 28 nm, which was an extremely small value compared to the crystallite size of the plate-like spinel particles obtained in Examples 1 to 6.
[0116] <Comparative Example 2> Synthesis of spinel particles S-b2 25 g of commercially available spinel particles (adjusted to an average particle diameter of 20 μm by sieving) were added with 25 g of alumina beads having a diameter of 5 mm, and the mixture was crushed using a paint conditioner to obtain 24.7 g of spinel particle powder. When the obtained powder was observed with an SEM (see FIG. 1(F)), it was found to be angular particles with irregular particle shapes and particle diameters. In addition, the average plate thickness was 5.3 μm, the average particle diameter calculated by a laser diffraction particle size distribution analyzer was 5.5 μm, and the aspect ratio calculated by the average particle diameter / average thickness was 1.0, which was extremely small compared to the aspect ratios of the plate-like spinel particles obtained in Examples 1 to 6. Furthermore, when an XRD measurement was performed, peak scattering due to spinel was observed. Using a CALSA detector, the crystallite diameter was calculated from the peak of the (311) plane observed around 37 degrees, and was 88 nm.
[0117] Evaluation method The α-alumina particles obtained in the above Synthesis Example and the spinel particles obtained in the above Examples and Comparative Examples were used as samples to carry out the following evaluations. Specific measurement methods are shown below. The evaluation results are shown in Table 1.
[0118] <Evaluation of α-alumina particles obtained in synthesis examples> [Measurement of the average particle size L of α-alumina particles] For the prepared samples, the average particle diameter d50 (μm) was determined using a laser diffraction particle size distribution analyzer HELOS (H3355) & RODOS (manufactured by Japan Laser Co., Ltd.) under conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar, and this was taken as the average particle diameter L.
[0119] [Analysis of Alpha Conversion Rate] The prepared sample was placed on a measurement sample holder with a depth of 0.5 mm, and packed flat with a constant load. It was then set in a wide-angle X-ray diffractometer (Rigaku Corporation, Rint-Ultma) and measured under the conditions of Cu / Kα radiation, 40 kV / 30 mA, scan speed of 2 degrees / min, and a scan range of 10 degrees to 70 degrees. The α conversion rate was calculated from the ratio of the strongest peak heights of α-alumina and transition alumina.
[0120] [Analysis of Mo content in α-alumina particles] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), about 70 mg of the prepared sample was placed on filter paper and covered with PP film for composition analysis. The amount of molybdenum determined from the XRF analysis results was calculated as molybdenum trioxide (mass%) relative to 100% by mass of the plate-like alumina particles.
[0121] [Density measurement] The prepared samples were pretreated at 300°C for 3 hours, and then measured using a Micromeritics dry automatic density meter, Accupic II1330, at a measurement temperature of 25°C and helium as the carrier gas.
[0122] <Evaluation of Spinel Particles Obtained in Examples and Comparative Examples> [Measurement of the average particle size L of spinel particles] For the prepared samples, the average particle diameter d50 (μm) was determined using a laser diffraction particle size distribution analyzer HELOS (H3355) & RODOS (manufactured by Japan Laser Co., Ltd.) under conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar, and this was taken as the average particle diameter L.
[0123] [Measurement of thickness T of spinel particles] The thickness of 50 samples thus prepared was measured using a scanning electron microscope (SEM), and the average value was used as the thickness T (μm).
[0124] [Aspect ratio L / T] The aspect ratio of the spinel particles was calculated using the following formula.
[0125] Aspect ratio = average particle size L of plate-like spinel particles / thickness T of plate-like spinel particles
[0126] [Analysis of Spinel Crystals] The prepared sample was placed on a measurement sample holder with a depth of 0.5 mm and filled flat with a constant load. It was then set in a wide-angle X-ray diffraction (XRD) device (Rigaku Corporation, Rint-Ultma) and measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 30 mA, scan speed of 2 degrees / min, and a scan range of 10 degrees to 70 degrees.
[0127] [Crystallite size measurement] Using a Rigaku Corporation X-ray diffractometer SmartLab and a CALSA detector, the crystallite diameter (nm) of the (311) plane was determined from the peak observed near 37 degrees under the following conditions.
[0128] (Measurement conditions) 2θ / θ method 2θ=15deg or more and 80deg or less Step number: 0.002 deg Scan speed: 0.05 deg. / min. βs=20rpm Soller / PSC=2.5deg.short Soller=2.5deg.
[0129] [Density measurement] The prepared samples were pretreated at 300°C for 3 hours, and then measured using a Micromeritics dry automatic density meter, Accupic II1330, at a measurement temperature of 25°C and helium as the carrier gas.
[0130] [Measurement of dielectric constant and dielectric loss tangent] 25 g of the prepared sample was added with 5 mm diameter alumina beads, and the sample was treated with a paint conditioner for 4 hours to pulverize the spinel particles. The dielectric constant and dielectric loss tangent of the pulverized spinel particles were measured using a vector network analyzer E8361A at a frequency of 1 GHz, a temperature of 25°C, and a humidity of 50% using a perturbation resonator method.
[0131] [Bending stress] The prepared sample was mixed to 66 wt% and polyphenylene sulfite resin (PPS resin, DIC MA-500) to 34 wt%, to prepare a total of 20 g of mixture. 20 g of the mixture was melt-mixed for 2 minutes using a twin-screw mixer equipped with a full-flight screw at an extruder temperature of 300°C and a screw rotation speed of 150 rpm. The resulting kneaded material was taken out of the die in a strand shape, pelletized, and then a dumbbell test piece with a width of 5 mm, a length of 75 mm, and a thickness of 1 mm was obtained using a small injection molding machine. The obtained test piece was supported at two points so that the distance between the supports was 32 mm, and a load was applied to the intermediate position of the two points on the side opposite to this at a crosshead movement speed of 1 mm / min, the maximum load at which the test piece broke was measured, and the three-point bending strength (MPa) was calculated. The bending strength was measured at five points to obtain an average value.
[0132] [Table 1]
[0133] From Table 1, a comparison between the spinel particles S-a1 obtained in Example 1 and the spinel particles S-a2 obtained in Example 2, and between the spinel particles S-a2 obtained in Example 2 and the spinel particles S-a4 obtained in Example 4 shows that the bending stress (bending strength) tends to increase as the crystallite size increases. Furthermore, a comparison of the spinel particles S-a2 obtained in Example 2, the spinel particles S-a5 obtained in Example 5, and the spinel particles S-a6 obtained in Example 6 revealed a tendency for the bending stress (bending strength) to increase as the aspect ratio increased.
[0134] In contrast, the spinel particles S-b1 obtained in Comparative Example 1 and the spinel particles Sb-2 obtained in Comparative Example 2 had smaller aspect ratios than the spinel particles S-a1 to S-a6 obtained in Examples 1 to 6. In particular, the spinel particles S-b1 obtained in Comparative Example 1 also had a smaller crystallite size and a significantly lower bending stress.
[0135] From the above, it has been demonstrated that the spinel particles of this embodiment have excellent mechanical properties while maintaining specific performance such as dielectric constant and dielectric tangent due to their high aspect ratio. [Industrial Applicability]
[0136] According to the plate-like spinel particles and the method for producing the same of this embodiment, it is possible to provide plate-like spinel particles that have excellent mechanical strength while maintaining a low dielectric tangent.
Claims
1. a thickness T of 0.01 μm or more and 5 μm or less, an average particle diameter L of 0.1 μm or more and 500 μm or less, an aspect ratio (L / T) of 3 or more and 500 or less, and molybdenum is contained within the particles; The plate-like spinel particles have a crystallite diameter of 60 nm or more and 90 nm or less, calculated from the half-width of a diffraction peak corresponding to a (311) plane obtained by X-ray diffraction method.
2. 2. The plate-like spinel particle according to claim 1, wherein the molybdenum content is from 0.01% by mass to 1% by mass in terms of molybdenum trioxide, relative to 100% by mass of the plate-like spinel particle.
3. A method for producing the plate-like spinel particles according to claim 1 or 2, comprising the steps of: A production method comprising calcining a magnesium compound and an aluminum compound in the presence of molybdenum.
4. The method according to claim 3 , wherein the aluminum compound is plate-like alumina particles.
5. The method according to claim 3 or 4, wherein the aluminum compound contains molybdenum in an amount of 0.1% by mass or more and 1% by mass or less in terms of molybdenum trioxide.
6. The method according to any one of claims 3 to 5, wherein a sodium compound or a potassium compound is used as a shape control agent during firing.
7. The method according to any one of claims 3 to 6, wherein the firing is carried out at a temperature of less than 1300°C.
8. The method according to any one of claims 3 to 7, wherein the aluminum compound and the magnesium compound have an average particle size of 1 µm or more and 10 µm or less.
Citation Information
Patent Citations
Spinel powder for light transmitting spinel sintered compact and its production
JP1994171930A
Heat-conductive composite oxide, heat-conductive resin composition and coating liquid
JP2016135841A
Tabular alumina particle and production method thereof
JP2016222501A
Heat conductive composite oxide, manufacturing method therefor and heat conductive composite oxide-containing composition
JP2017190456A
Spinel particles, method for producing same, and composition and molding including spinel particles
WO2016148236A1